MATHEMATICAL FORMULA PROGRAM APPLICATION VISUALIZATION AND EXERCISE ROOM AND CONSTRUCTION PROBLEMS USING INTERACTIVE VISUAL BASIC 6.0 - Putri Soraya; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2006)
In the current era of globalization developments in science, technology and information increasingly fast and sophisticated. Many all fields associated with the computer because with knowledge of various computer performance is sought here. With easy to obtain such knowledge, the authors are interested in creating a collection of mathematical applications using Visual Basic 6.0. This application is made to meet the learning needs of students bagiu because the author saw the students are still extremely difficult to learn the formula wake up much less to memorize formulas are in addition they also collided with the existing curriculum so that did not have time to explore and understand more about the formula up mathematics, using electronic media, the author hopes they can better understand the mathematical formulas and not wake up again consider the specter to be feared.